The Outsider - Tarr, Béla; Mihók, Barna; Pap, Ferenc; Szabó, András; Fodor, Jolan; Donko, Imre (Facets Video, 2005)
Self-absorbed and aimless, Andras lacks direction and purpose in his life. He leaves his job as a male nurse to drift into a factory job; he marries a woman he does not love, though he has fathered a child by another. His only escape is drinking with his friends and playing music at the local clubs and taverns. "Great artists like Beethoven lived along, they never married," he tells his wife, but that becomes a excuse to idle his time away playing the violin. Celebrated for his nihilistic tales of desperate people unable to escape their human or social conditions, Tarr is one of the most distinctive talents in world cinema. With "The Outsider" he extends the documentary style of "Family Nest". Shot mostly in close-ups, his films communicate a world of limited options and few opportunities. His characters are trapped in cramped apartments and tedious jobs, dealing with problems of relationships, family, and work. "The Outsider" is the drama of modern life as it is lived. [Cover]
Keywords: DVD-Video